Procedure to Reduce Evaluation Time in the Selection of Professional Staff in Medium-Sized Multi-Family Construction Companies Using the AHP Method - Huamani, Diana Conislla (2025)
In the construction sector, the selection of personnel for the technical office faces challenges such as the lack of structure and subjectivity in the evaluation criteria, which makes it difficult to quickly identify the most suitable candidates. This article proposes an optimized procedure to address this problem through the use of the AHP multicriteria method and Expert Choice software. The process involves applying AHP to establish priorities and evaluate candidates based on previously defined objective criteria. Through interviews and surveys, deficiencies in the traditional approach were identified, such as the lack of planning and the reliance on subjective judgments. The proposal demonstrates how the application of AHP reduces the evaluation time by 70%, improving transparency, traceability, and reliability of the process, contributing to the formation of technical teams more aligned with the specific requirements of the projects.